PENGARUH KUALITAS AUDIT, KOMITE AUDIT, LEVERAGE, DAN UKURAN PERUSAHAAN TERHADAP MANAJEMEN LABA: Studi Empiris pada perusahaan manufaktur yang terdaftar di Bursa Efek Indonesia - I Gede Tarsan Subali; Gde Herry Sugiarto Asana; Sarita Vania Clarissa (Journal Research of Accounting, 2021)
This study aims to examine the effect of audit quality, audit committee, leverage, and firm size on earnings management in manufacturing companies listed on the Indonesia Stock Exchange. This study uses secondary data. Data is collected from the Indonesia Stock Exchange and the annual financial reports from 2017-2019. The data collection method used was purposive sampling method with a total sample of 60 companies. Data analysis techniques used are multiple linear regression. Based on the results of the study, it is concluded that audit quality has a negative and significant effect on earnings management, the audit committee has a negative and significant effect on earnings management, leverage has a positive and significant effect on earnings management, firm size has a positive and significant effect on earnings management